Penggunaan Media Komik untuk Meningkatkan Motivasi dan Prestasi Belajar Bahasa Arab Kelas VII di Madrasah Mu’alimin Mu’alimat Denanyar - Rahmawati, Rina Dian; Oktavianti, Devi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
In the world of education, reading is a must for students. Because reading is the main tool for achieving learning goals. Many students complain that learning a foreign language is very difficult. There are several factors that cause difficulty in learning a foreign language, including the level of foreign language mastery, motivation, lack of practice, lack of learning media, and creativity in textbooks. This study aims to determine the difference between students' learning motivation and learning ability before and after using comic media. The research method used is Research & Development with the Borg & Gall Model which includes 10 steps. The results of the study are (1) based on the validation test of material and language experts, this comic has a very good quality (SB), with a result of 88%, (2) based on a small-scale trial, the student's response to this product was strongly agree (SS), with a score of 97.5%, and the test on a field scale student response to this product was strongly agree (SS), with a score of 93 .3%, (3) there are differences in student learning outcomes when using comic media, namely the results of students' post-test and pre-test scores. With the average result of the pre-test of students 20.75 and the average result of the post-test of students 82. Seeing from the average post-test of students who are superior to the pre-test of students, it can be said that the Arabic-Indonesian comic media is effectively used and can improve the ability to learn Arabic.